Storage Ratio of CO2 Miscible Flooding in Chang 8 Reservoir of H Block in Ordos Basin Under Different Injection Methods - Zhang, Yi; Zhang, Bin; Yang, Yongzhi; Liu, Banghua; Shen, Lei (Frontiers in Energy Research, 2022)
Carbon dioxide is a typical kind of greenhouse gases and the oil and gas field recovery ratio could be significantly improved by injecting it into the formation. The main goal is to increase the recovery ratio in the early stage of studying gas injection miscible flooding. With the advancement of "carbon neutral" strategy in China, the application of CO2 miscible flooding technology which is in order to enhance oil recovery ratio in Chinese oilfields has been further expanded. The development concept needs to change from simply improving the recovery ratio to both the recovery ratio and the CO2 storage ratio. In order to study the recovery and storage ratio of CO2 miscible flooding with different injection methods, this paper studies the CO2 storage of the Chang 8 reservoir in Block H of the Ordos Basin. Firstly, the minimum miscible pressure of CO2 at formation temperature was measured by the thin tube experiment according to the reservoir pressure status to judge the CO2 flooding status in study area. Then, the numerical simulation model of the study area was established, and the historical fitting was completed according to the existing CO2 flooding test wells. The reservoir numerical simulation is used to study the recovery ratio and CO2 storage ratio under different CO2 miscible flooding, including different injection rate, injection sequence and bottom hole pressure. The results show that the minimum miscible pressure of CO2 in study area is between 12.65-14.80 MPa which means the CO2 flooding state in this area is miscible flooding with high oil displacement efficiency. The CO2 storage ratio at 5-40t/d CO2 injection rate is between 54.02%-64.38% after 20 years, and the CO2 storage ratio is larger when the gas injection rate is 10t/d. The CO2 storage ratio after 20 years under different gas injection sequences is 57.69%-61.27%. It is recommended that the study area adopt water-gas alternate injection sequence. When continuous gas injection is used, the CO2 storage ratio under different production well bottom hole pressures is between 54.95%-59.82%. It is recommended that the bottom hole flow pressure in the study area be maintained at about 10 MPa.